Partial splenectomy followed by total splenectomy in thalassemia (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Total splenectomy is the usual operative practice for children with thalassemia requiring splenectomy. But wherever possible, the surgical community should carefully consider partial splenectomy as an alternative treatment option that may offer few important benefits to the patient with the same indication. Here, we are reporting a case where a thalassemic boy enjoyed six years free from overwhelming post-splenectomy infection after partial splenectomy without any vaccination or prophylactic antibiotic before eventual total splenectomy. So, partial splenectopmy may be considered as a preferable initial treatment option for the thalassemic patient with splenomegally requiring splenectomy.